¡Miranos! (Look at Us! We Are Healthy!): Home-Based and Parent Peer–Led Childhood Obesity Prevention. Issue 5 (September 2016) - Sosa, Erica T.; Parra-Medina, Deborah; He, Meizi; Trummer, Virginia; Yin, Zenong
Parent interventions for childhood obesity prevention have traditionally experienced low participation rates or used passive methods such as newsletters. In contrast, the ¡Miranos! intervention home-based activities included parent-led face-to-face meetings delivered after school, take-home bags with educational materials, and scavenger hunt games to deliver health information to Head Start families regarding nutrition, physical activity, and healthy growth promotion for their preschooler. This study employed a quasi-experimental design with three intervention centers (two that received only center-based activities and one that received center- and home-based activities) and one comparison center. Data were collected on participating Head Start children and their parents/guardians and included parent attendance, parent health message recall through intercept interviews, parent knowledge through pre- and posttests, and family supportive behaviors and child health behaviors through a parent questionnaire. Parents/guardians that received both center- and home-based activities significantly increased knowledge scores (t = 2.50, degrees of freedom = 123, p < .05) and family supportive behaviors from baseline to follow-up (t = 2.12, degrees of freedom = 122, p < .05). This study demonstrates the effects home-based interventions can have when coupled with center-based activities and implemented in the center at the end of the school day.